KRITERIA BUNGA MENJADI POLONG BERNAS PADA BEBERAPA VARIETAS KACANG TANAH (ARACHYS HIPOGAEA L.) - Sufianto . (Jurnal Gamma, 2011)
SufiantoStaf Pengajar Jurusan Agroteknologi, Fakultas Pertanian Peternakan, Universitas Muhammadiyah MalangAlamat Korespondensi : Perum.Joyogrand I/52 RT 01 RW 08 MalangEmail: sufianto@umm.ac.idABSTRACTInterest criteria to be bernas’ pods in peanut varieties to determine the level of outcome forfarmers. This is because not all the flowers that appear to be a bernas’ pods. Naturally, the processinitiated pod formation appears that fertilized flowers and so ginophore, then moves into the soilsurface to form a pod.The problem though interest has been fertilized but no guarantee will be pithy pods. So pleasenote that criteria of interest has been matured that can be pithy pods. The purpose of this study todetermine the criteria of interest in several varieties that can be pithy pods thirty days after flowering.The results showed that the criteria of interest that can be higher pithy pods are varieties ofwhich Lamb creteria of flowers are the flowers appear earlier, lies in the segment 1-4, the amount ofinterest that arise during the 30 days of flowering reaches 127 96 Interest and the fertilized flower,ginophore rise less than 3 days after flowering, ginophore speed reaches the soil surface 2-3 cm perweek, number of pods per plant pithy reached 65 with the pithy pods per plot reached 47.82 kg.Keywords: Flowers, pods pithy and varieties